PELATIHAN KERAJINAN TANGAN MENGGUNAKAN BAHAN RECYCLE UNTUK MELATIH KETERAMPILAN ANAK DESA SETIA JAYA - Anisa Aryunita; Arrahim Arrahim; Novita Puspahaty (An-Nizam, 2023)
Plastic and paper waste is waste that is very difficult to decompose, because plastic waste is always everywhere, both in rural and urban areas as a result of human activity and population density in Indonesia because it affects the increase in plastic waste and paper waste, waste that is difficult to decompose is plastic waste, for example disposable plastic straws and currently plastic waste is intended to be used as handicraft material because it can produce high selling points and in this study the authors use used plastic straws to be used as wall hangings to generate selling points to reduce the amount of plastic waste in Indonesia, so that children don't feel bored in learning which contains more material than handicrafts like this, with this program we hope that Indonesia will not have too much plastic waste and can help children become in productive.